A Comparative Study of Fluticasone Alone and Fluticasone with Azelastine Nasal Spray in Patients with Allergic Rhinitis - Fidelis G. Dass A; Sahana G N; Nalini GK; Ragavendra Prasad KU (Universitas Padjadjaran, 2021)
In India, 20-30% of the population suffers from allergic rhinitis. Its prevalence increasing over the past many years and often adversely affects the quality of life. Little importance is given to allergic rhinitis and patients fail to correlate the ill-health to symptoms of allergic rhinitis in India. Studies have shown that patients with allergic rhinitis adversely affect the behavior, work performance, and lifestyle of patients. Hence this study was undertaken to compare the efficacy of fluticasone alone and in combination with azelastine. A total of 60 patients were randomly assigned into two groups (30 patients each), where the first group received fluticasone and the other group received fluticasone + azelastine. Drugs were administered as nasal spray and improvement were assessed using Total Nasal Symptom Score (TNSS) and Quality of life was assessed using Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) at baseline and at 2 weeks. Descriptive statistics and student's t-test was used to analyze data. Both the groups had statistical improvement in TNSS and RQLQ scores when compared to baseline within the groups (p < 0.0001). Comparison of overall TNSS between the groups was statistically significant (p < 0.001), though total RQLQ scores were insignificant (< 0.02) when compared between two groups. It was observed that both drugs were safe and efficacious. By these results, we conclude that the combination therapy showed better improvement in TNSS when compared to fluticasone alone. Azelastine due to antihistaminic properties and fluticasone anti-inflammatory effect showed synergistic anti-inflammatory effect and improvement in quality of life